A novel model of urosepsis in rats developed by injection of Escherichia coli into the renal pelvis - Cao, Yuanfei; Bai, Can; Si, Penghui; Yan, Xin; Zhang, Peng; Yisha, Zuhaer; Lu, Peixiang; Tuoheti, Kuerban; Guo, Linfa; Chen, Zhao; Bai, Xiaojie; Liu, Tongzu (Frontiers in Immunology, 2023)
Despite extensive research, urosepsis remains a life-threatening, high-mortality disease. Currently, animal models of urosepsis widely accepted by investigators are very scarce. This study aimed to establish a standardized and reproducible model of urosepsis in rats. Forty adult Wistar rats were randomly divided into four groups according to the concentration of injected E. coli suspensions: Sham, Sep 3×, Sep 6×, and Sep 12×. Because the ureter is so thin and fragile, no conventional needle can be inserted into the ureter, which is probably why rats are rarely used to develop models of urosepsis. To solve this problem, the left ureter was ligated in the first procedure. After 24 hours, the left ureter above the ligation was significantly dilated, then saline or different concentrations of E. coli at 3 ml/kg were injected into the left renal pelvis using a 30G needle. The left ureter was subsequently ligated again at a distance of 1 cm from the renal hilum to maintain high pressure in the renal pelvis. Following injection of E. coli or saline for 24 h, three rats from each group were sacrificed and their organs (lung, liver, and right kidney) were collected. In contrast, the remaining seven rats continued to be observed for survival. At 10 days after E. coli injection, rats in the sep12× group had a higher mortality rate (100%) compared to the sep3× group (28.6%) or the sep6× group (71.4%). The significant changes in peripheral blood WBC count, serum IL-6 and TNF-α levels were also in the sep12× group. In addition, rats in the sepsis group showed multi-organ dysfunction, including damage to the lungs, liver, and kidneys. The establishment of a standardized rat model of urosepsis may be of great value for studying the pathophysiological of urosepsis.